2020
DOI: 10.1101/2020.06.13.20130294
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Impact of social distancing measures for preventing coronavirus disease 2019 [COVID-19]: A systematic review and meta-analysis protocol

Abstract: Introduction: Social distancing measures (SDMs) protect public health from the outbreak of coronavirus disease 2019 (COVID-19). However, the impact of SDMs has been inconsistent and unclear. This study aims to assess the effects of SDMs (e.g. isolation, quarantine) for reducing the transmission of COVID-19. Methods and analysis: We will conduct a systematic review meta-analysis research of both randomised controlled trials and non-randomised controlled trials. We will search MEDLINE, EMBASE, Allied & Co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 49 publications
0
12
0
Order By: Relevance
“…In fact, the COVID-19 has generated https://doi.org/10.1017/jmo.2021.15 uncertainty. Some authors go so far as to predict the COVID-19 endemic (Regmi & Lwin, 2020) while many economists predict the outcomes of this pandemic will remain till 2021 (Akkermans, Richardson, & Kraimer, 2020). Currently, no one knows when this virus will end and if its consequences on the work patterns in organizations will be temporary or permanent (Bartik, Cullen, Glaeser, Luca, & Stanton, 2020), even after the recent development of different types of vaccines (Yu et al, 2021).…”
Section: Covid-19 and Strategic Human Resource Managementmentioning
confidence: 99%
“…In fact, the COVID-19 has generated https://doi.org/10.1017/jmo.2021.15 uncertainty. Some authors go so far as to predict the COVID-19 endemic (Regmi & Lwin, 2020) while many economists predict the outcomes of this pandemic will remain till 2021 (Akkermans, Richardson, & Kraimer, 2020). Currently, no one knows when this virus will end and if its consequences on the work patterns in organizations will be temporary or permanent (Bartik, Cullen, Glaeser, Luca, & Stanton, 2020), even after the recent development of different types of vaccines (Yu et al, 2021).…”
Section: Covid-19 and Strategic Human Resource Managementmentioning
confidence: 99%
“…Some studies believe that social distancing cuts off the transmission path of the virus, thereby reducing R 0 [ 23 ]. Moreover, different mathematical models and simulations have displayed a good correlation with the data showed in biomedical studies, which offered a high level of evidence for the impact of social distancing measures to contain the pandemic [ 24 , 25 ]. For example, based on simple stochastic simulations, Cano et al [ 26 ] evaluated the efficiency of social distancing measures to tackle the COVID-19 pandemic.…”
Section: Introductionmentioning
confidence: 99%
“…4 Considering the contagious nature of COVID-19, World Health Organization (WHO) introduced the concept of social distancing as a measure to reduce the transmission of infection. 5 This concept was widely appreciated as world history showed that exercising quarantine can help battle against and grip the spread of infectious disease such as cholera, the plague, Ebola, and severe acute respiratory syndrome (SARS). 6 With the same concept, Pakistani government enforced gradual shutdown of schools, universities, and various industries from 16th March, eventually prohibiting all nonessential activities from March 21, 2020.…”
Section: Introductionmentioning
confidence: 99%